1993
DOI: 10.1002/bit.260420405
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody productivity and the metabolic pattern of perfusion cultures under varying oxygen tensions

Abstract: The metabolic pattern and cell culture kinetics of high-cell-density perfusion cultures were compared under two different oxygen transfer conditions: oxygen limiting and not limiting. When oxygen was a limiting factor during perfusion culture, both specific glucose uptake and lactate production rates increased, compared to non-oxygen-limited condition, by about 60% and 30%, respectively. The specific glutamine uptake rate under oxygen-limited conditions was almost 4.0 times higher than that under non-oxygen-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The significant reduction in the growth rate of E1B-19K-expressing cells was also reflected in an increase in the perfusion to batch q MAb ratio. Indeed, many mammalian cell lines cultivated in perfusion exhibit an increase in specific MAb productivity under such slow growth conditions (Al-Rubeai et al, 1992;Banik and Heath, 1995;Batt et al, 1990;de la Broise et al, 1991de la Broise et al, , 1992Johnson et al, 1996;Hansen et al, 1993;Mercille et al, 1994a-c;Shi et al, 1993;Tokashiki and Takamatsu, 1993;Trampler et al, 1994). The q MAb has been shown to be cell cycle dependent and optimum in the G 1 (Byars and Kidson, 1970;Cazzador and Mariani, 1993;Garatun-Tjeldsto et al, 1976;Linardos et al, 1992;Mercille and Massie, 1998;Ramirez and Mutharasan, 1990;Richieri et al, 1991;Suzuki and Ollis, 1989) or G 2 /M phase (Cherlet et al, 1995;Kromenaker and Srienc, 1991;Mercille and Massie, 1998;Watanabe et al, 1973).…”
Section: Effect Of E1b-19k On Productivity In Perfusion Culturementioning
confidence: 93%
“…The significant reduction in the growth rate of E1B-19K-expressing cells was also reflected in an increase in the perfusion to batch q MAb ratio. Indeed, many mammalian cell lines cultivated in perfusion exhibit an increase in specific MAb productivity under such slow growth conditions (Al-Rubeai et al, 1992;Banik and Heath, 1995;Batt et al, 1990;de la Broise et al, 1991de la Broise et al, , 1992Johnson et al, 1996;Hansen et al, 1993;Mercille et al, 1994a-c;Shi et al, 1993;Tokashiki and Takamatsu, 1993;Trampler et al, 1994). The q MAb has been shown to be cell cycle dependent and optimum in the G 1 (Byars and Kidson, 1970;Cazzador and Mariani, 1993;Garatun-Tjeldsto et al, 1976;Linardos et al, 1992;Mercille and Massie, 1998;Ramirez and Mutharasan, 1990;Richieri et al, 1991;Suzuki and Ollis, 1989) or G 2 /M phase (Cherlet et al, 1995;Kromenaker and Srienc, 1991;Mercille and Massie, 1998;Watanabe et al, 1973).…”
Section: Effect Of E1b-19k On Productivity In Perfusion Culturementioning
confidence: 93%
“…On the other hand, limiting DOT (below 2%) increases hybridoma viability (Miller at al., 1988;Ozturk and Palsson, 1990). The specific monoclonal antibody (MAb) production rate has been shown to remain constant throughout a wide range of DOT (Ozturk and Palsson, 1991;Shi et al, 1993), although an optimum DOT between 10% and 80% has been reported for MAb concentration (Ozturk and Palsson, 1991). In contrast to the relatively abundant reports of the effect of constant DOT on hybridoma metabolism, physiology, and culture performance, no information exists for the case of fluctuating DOT.…”
Section: Introductionmentioning
confidence: 96%
“…In hybridomas, which exhibit a high glycolytic activity even in aerobic conditions, oxygen determines the consumption rates of carbon and energy sources (glucose and glutamine) and the production of toxic metabolites such as lactate and ammonia (Miller et al, 1988;Ozturk and Palsson, 1991;Shi et al, 1993). The intracellular redox state is also a function of DOT (Hevehan and Miller, 1999;Zupke et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Extensive studies on the growth and antibody production characteristics of hybridomas have revealed that antibody secretion is not growth-associated, but rather that these cells exhibit higher speciÂźc productivities during the late phase of batch cultures (De la Boise et al, 1991;Flickenger et al, 1990;Shi et al, 1993). However, it is now well established that the conditions of nutrient deprivation observed at the late stage of batch cultures can induce apoptotic death of B-cell hybridomas and thus limit antibody productivity (Duval et al, 1990;Mercille et al, 1994b;Perreault and Lemieux, 1993b;Vomastek and Franek, 1993).…”
Section: Introductionmentioning
confidence: 97%